2008
DOI: 10.1051/0004-6361:20078821
|View full text |Cite
|
Sign up to set email alerts
|

The unusual Nova Cygni 2006 (V2362 Cygni)

Abstract: Context. Optical nova lightcurves often have structures, such as rapid declines and recoveries, due to nebular or dusty phases of the ejecta. Nova Cygni 2006 (V2362 Cyg) underwent an unusual brightening after an early rapid decline. The shape of the lightcurve can be compared to that of V1493 Aql, but in that case the whole event was not as bright and only lasted a couple of weeks. V2362 Cyg had a moderately fast decline of t 2 = 9.0 ± 0.5 days before rebrightening, which lasted 250 days after maximum. Aims. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 14 publications
(17 reference statements)
1
23
4
Order By: Relevance
“…While V597 Pup showed a gradually declining light curve, V2491 Cyg showed an unusual second rebrightening with ∼2 mag amplitude peaking after about 17 days of the main outburst. The nature of this second mini‐outburst is rather similar to those observed in V1493 Aql and V2362 Cyg (Venturini et al 2004; Kimeswenger et al 2008). From the light curves, we estimate t 2 to be 2.5 and 5 d for V597 Pup and V2491 Cyg, respectively, which indicates that they are fast novae.…”
Section: Observations and Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…While V597 Pup showed a gradually declining light curve, V2491 Cyg showed an unusual second rebrightening with ∼2 mag amplitude peaking after about 17 days of the main outburst. The nature of this second mini‐outburst is rather similar to those observed in V1493 Aql and V2362 Cyg (Venturini et al 2004; Kimeswenger et al 2008). From the light curves, we estimate t 2 to be 2.5 and 5 d for V597 Pup and V2491 Cyg, respectively, which indicates that they are fast novae.…”
Section: Observations and Analysissupporting
confidence: 80%
“…The optical light curve of V2491 Cyg resembles that of two other novae, V1493 Aql and V2362 Cyg, in terms of the presence of a secondary peak. The secondary peaks in V2491 Cyg and V1493 Aql (Venturini et al 2004) were observed about 16 and 48 days after the primary outburst, respectively, where as in case of V2362 Cyg it was after ∼240 days (Kimeswenger et al 2008). Among these three novae, the SSS phase has been detected in V2491 Cyg (this work) and V2362 Cyg (Hernanz, Ferri & Sala 2007).…”
Section: Discussionmentioning
confidence: 98%
“…The UBV data are taken from Munari et al (2008b), V and visual from the AAVSO and VSOLJ archives. V2362 Cyg reached m V,max = 7.8 at optical maximum and then declined with t 2 = 9.0 ± 0.5 and t 3 = 21.0 ± 0.5 days (Kimeswenger et al 2008). For the first 60 days, the decline down to 12th magnitude is smooth and resembles a power-law decline.…”
Section: V2362 Cyg 2006mentioning
confidence: 82%
“…For the first 60 days, the decline down to 12th magnitude is smooth and resembles a power-law decline. Then it rose up again to 10th magnitude (secondary maximum) about 240 days after the discovery, and suddenly dropped to 13th magnitude in ∼ 20 days, followed by the formation of an optically thin dust shell (Arai et al 2010), and again slowly declined resembling a power law before the secondary maximum (e.g., Kimeswenger et al 2008). An orbital period of 1.58 hr was suggested by Balman et al (2009).…”
Section: V2362 Cyg 2006mentioning
confidence: 99%
“…Here, we reexamine it on the (B − V ) 0 -(M V − 2.5 log f s ) diagram. V2362 Cyg shows a prominent secondary maximum (e.g., Kimeswenger et al 2008;Munari et al 2008b, see Figure 43). The origin of the secondary maximum was discussed by Hachisu & Kato (2009).…”
Section: V2362 Cyg 2006mentioning
confidence: 99%